PENERAPAN METODE DRILL PADA MATA PELAJARAN EKONOMI PADA SISWA KELAS XI SMA SANTUN UNTAN - Ariyanto, Arif; Witarsa, Witarsa; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine whether or not there is an increase in results student learning by applying drill methods on economic subjects to students class XI IPS 1 SMA Santun Untan Pontianak. The method used in the study this is an experimental method with quantitative research. Data source inside this study was IPS 1 XI class students and the population in this study amounted to 27 students from the XI IPS 1 SMA Santun Untan Pontianak. Data obtained with using data colletion techniques in the from of interview, observation sheet (check list) and test sheets in the form of writing items question, validity and reliability. Based on data analysis techniques using the t-test Paired Sample t test is the value of the count for student learningoutcomes is -9,635 with probability (Sig.) 0,000. Because the probability (Sig.) 0,000 < 0,05, then Ho is rejected and Ha be accepted. This means that there is a significant increase in the implementation of the drill method towards the learning outcomes of students of class XI IPS 1 SMA Santun Untan Pontianak. Based on the results of the processing, it can be concluded that the application of teh drill method make a significant influence on student learning outcomes on subjects economy in class XI IPS SMA Santun Unan Pontianak.Keywords: (Application, Drill Method, Economic Subject)